Manifestation of helicity in one-dimensional iodobismuthate. Issue 21 (10th May 2016) - Pandey, Souvik; Andrews, Alex P.; Venugopal, Ajay
Abstract : The first example of an inorganic–organic hybrid material incorporating a helical iodobismuthate [BiI4 ]∞ is presented. Abstract : We report here, the first example of an inorganic–organic hybrid material incorporating a helical iodobismuthate [BiI4 ]∞ templated by 2, 6-diisopropylanilinium cations. The realisation of the helical iodobismuthate opens up the possibility of a wide range of physical properties among hybrid materials.